Leptobotia bellacauda, a new species of loach from the lower Yangtze basin in China (Teleostei: Cypriniformes: Botiidae) - Bohlen, Jörg; Šlechtová, Vendula (Zootaxa, 2016)
A new species, Leptobotia bellacauda is described from the lower Yangtze River basin. The new species is distinguished from all other species of Leptobotia by a combination of the following characters: body plain brown, prominent black bar in caudal fin, dorsal half of head dusky black, ventral half of head cream colour, eye well developed, lobes of caudal fin rounded, origin of pelvic fins beneath or anterior to dorsal-fin origin, and pectoral fin in adult males enlarged, with numerous tubercles.